Diagnostic Yield of Electromagnetic Navigation Bronchoscopy Using a Curved-tip Catheter to Aid in the Diagnosis of Pulmonary Lesions. Issue 1 (January 2017) - Mukherjee, Sumit; Chacey, Michael
Abstract : Background: Electromagnetic navigation bronchoscopy (ENB) may aid in the diagnosis of solitary pulmonary lesions with a lower complication rate than conventional diagnostic modalities. A curved-tip catheter is now available for use with ENB; however, the diagnostic yield of this device has not been previously reported. Methods: A single-center, single-operator retrospective chart review was performed on patients who underwent ENB for the diagnosis of pulmonary lesions. A curved-tip catheter was used in all procedures; angle options were chosen depending on lesion location. After navigation to the target lesion, fine-needle aspiration, brushings, biopsies, and bronchoalveolar lavage were performed in all patients. Correct localization was confirmed with fluoroscopy. Results: Thirty-one consecutive patients underwent ENB between February and October 2014. The mean lesion size was 1.8 cm (range, 0.4 to 4.0 cm) and 35% were in the right upper lobe. The probe tip was navigated to the target lesion in all cases. A diagnosis was obtained in 30/31 patients (96.8%). Twenty-two (71%) had a definitive histologic diagnosis of malignancy. One case was nondiagnostic requiring a repeat fine-needle aspiration. The remaining 8 nonmalignant cases were followed radiologically and demonstrated no progression of lesion size through at least 1 year. Fiducials were placed in 48% of cases. There were 2 pneumothoraces (6.5%), one of which required chest tube placement (3.2%). Conclusions: This study suggests that the curved-tip catheter is a useful modality for diagnosing peripheral pulmonary lesions with ENB. The diagnostic yield of ENB using this catheter was superior to that reported in other studies utilizing straight catheters.